Pemanfaatan Media Cerita Bergambar untuk Meningkatkan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Rohyana, Hadi; Muttaqin, Muhammad Fauzan; Rahayu S, Putri (Jurnal Likhitaprajna, 2024)
This study aims to explore the effectiveness of picture story media in improving the learning outcomes of fourth-grade elementary school students. The use of visual media in the learning process is expected to enhance students' interest and learning outcomes in the material presented. The research method employed is classroom action research (CAR). The subjects of this study were 31 fourth-grade students at Bani Saleh Elementary School in Bekasi city. Data were collected through observation, interviews, learning outcome tests, and student response questionnaires. The results of the study indicate that the use of picture story media significantly improves students' learning outcomes. The average test scores of students showed a significant increase after the implementation of picture story media. Additionally, student responses to the use of this media were very positive; they felt more interested and motivated in participating in the lessons. Thus, picture story media proved effective as a learning aid that can enhance students' learning outcomes. This study recommends that elementary school teachers consider using picture story media as an alternative creative and innovative teaching strategy to improve the quality of classroom learning.